2009
DOI: 10.1055/s-0029-1210974
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Peripheral Insulin Sensitivity in Acromegalic Patients

Abstract: In 13 nondiabetic acromegalic patients glucose homeostasis was studied by use of the hyperglycaemic clamp technique and compared to a group of sex and age matched and a group of sex, age and weight matched controls. When compared to a control group of normal weight glucose stimulated insulin release (I) was significantly increased and tissue sensitivity to insulin (M/I) significantly decreased. However, no significant differences were observed when the parameters were compared with a weight matched group. Gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…A number of previous studies have investigated the correlations of GH and IGF‐1 with specific co‐morbidities in patients with treated acromegaly, but have yielded inconsistent results. For example, both GH and IGF‐1 have been shown to correlate with insulin resistance 6–9 . However, there is conflicting evidence on which is the better predictor of insulin resistance 10–12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of previous studies have investigated the correlations of GH and IGF‐1 with specific co‐morbidities in patients with treated acromegaly, but have yielded inconsistent results. For example, both GH and IGF‐1 have been shown to correlate with insulin resistance 6–9 . However, there is conflicting evidence on which is the better predictor of insulin resistance 10–12 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, both GH and IGF-1 have been shown to correlate with insulin resistance. [6][7][8][9] However, there is conflicting evidence on which is the better predictor of insulin resistance. [10][11][12] Furthermore, several studies have found no correlation between GH or IGF-1 with co-morbidities associated with acromegaly including hypertension, blood pressure, glucose tolerance and arthropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Both GH deficiency and GH excess are associated with disturbances of carbohydrate metabolism (26). Therefore special attention has been paid to changes in glucose and HbA 1c concentrations as well as glucose metabolism in GH-deficient patients during GH replacement therapy (GHRT).…”
mentioning
confidence: 99%
“…Like acromegaly, cushing syndrome can be caused by pituitary adenoma, which is the case in 70% of cushing syndrome incidences [29]. Clinical associations were previously reported for acromegaly and obesity [30] as well as for obesity and PCOS [31,32]. Cachexia has manifestations that are adverse to obesity, such as loss of weight.…”
Section: Resultsmentioning
confidence: 99%